Effects of reducing sedentary behavior on cardiorespiratory fitness in adults with metabolic syndrome: A 6-month RCT - Norha Jooa; Sjöros Tanja; Garthwaite Taru; Laine Saara; Saarenhovi Maria; Kallio Petri; Laitinen Kirsi; Houttu Noora; Vähä-Ypyä Henri; Sievänen Harri; Löyttyniemi Eliisa; Vasankari Tommi; et al. (John Wiley and Sons Inc, 2025)
Introduction:
Poor cardiorespiratory fitness (CRF) is associated with adverse health outcomes. Previous observational and cross-sectional studies have suggested that reducing sedentary behavior (SB) might improve CRF. Therefore, we investigated the effects of a 6-month intervention of reducing SB on CRF in 64 sedentary inactive adults with metabolic syndrome in a non-blind randomized controlled trial.
Materials and Methods:
In the intervention group (INT, n = 33), the aim was to reduce SB by 1 h/day for 6 months without increasing exercise training. Control group (CON, n = 31) was instructed to maintain their habitual SB and physical activity. Maximal oxygen uptake (VO2max) was measured by maximal graded bicycle ergometer test with respiratory gas measurements. Physical activity and SB were measured during the whole intervention using accelerometers.
Results:
Reduction in SB did not improve VO2max statistically significantly (group × time p > 0.05). Maximal absolute power output (Wmax) did not improve significantly but increased in INT compared to CON when scaled to fat free mass (FFM) (at 6 months INT 1.54 [95% CI: 1.41, 1.67] vs. CON 1.45 [1.32, 1.59] Wmax/kgFFM, p = 0.036). Finally, the changes in daily step count correlated positively with the changes in VO2max scaled to body mass and FFM (r = 0.31 and 0.30, respectively, p < 0.05).
Discussion:
Reducing SB without adding exercise training does not seem to improve VO2max in adults with metabolic syndrome. However, succeeding in increasing daily step count may increase VO2max.